PEMBERANTASAN PEREDARAN NARKOTIKA DIKALANGAN REMAJA - Abdul Rahman Binda; Rahayu Kojongian; Gamlan Dagani (Halu Oleo University, 2024)
This study aims to explore more effective eradication strategies by examining causal factors, evaluating existing policies, and formulating steps to improve prevention and enforcement efforts. This research method combines normative and empirical approaches to determine the Eradication of drug trafficking among adolescents. The normative approach includes the study of relevant laws, cases, laws, and historical developments. The results of the study indicate that drug trafficking among adolescents is influenced by social and family environmental factors, and the lack of education about the dangers of narcotics, which leads to serious physical, psychological, and social impacts. Eradication efforts require a comprehensive approach through education and public campaigns, strengthening the role of families in supervision and communication, rehabilitation for user recovery, and strict law enforcement against drug dealers. Synergy between the government, families, schools, law enforcement, and the community is essential, by utilizing information technology to raise awareness and reach adolescents more effectively.